UNUSUAL CASE OF A SURVIVOR OF A SELF-INFLICTED SUICIDAL CUT-THROAT INJURY (Journal of Forensic Medicine & Toxicology, 2022)
Death by suicide is common among younger age groups and the methods to commit vary from less painful to more violent and agonizing acts. Slashing the throat with a sharp-edged weapon is the least frequent suicidal method. In the present case, a 30-year-old male attempted suicide by self-inflicting cut-throat injury with a kitchen knife. The injury was a single linear incised wound situated in zone 2 of the neck zones as classified by Roon and Christensen. The margins of the wound were not clean cut but irregular and coinciding with the superior neckline and were placed nearly symmetrically on both sides of the neck. The injury was deeper at the start and superficial at its end on the right side. The patient was operated in the emergency trauma operation theatre (OT) where it was observed that the deeper tissues of the neck including the floor of the mouth and thyroid cartilage were cut however the trachea was spared. Deaths due to suicidal or homicidal cut-throat injuries are regularly encountered by autopsy surgeons, however, it is rare to encounter a self-inflicted cut-throat injury where the victim survived the neck injury in a clinical forensic setting.
Keywords: Cut-throat; Survival; Case reports